Comparison of vaginal flora after treatment with a clotrimazole 500 mg vaginal pessary or a fluconazole 150 mg capsule for vaginal candidosis. Issue 3 (June 1991) - Boag, F C; Houang, E T; Westrom, R; McCormack, S M; Lawrence, A G
Abstract : The effect of antifungal therapy on the vaginal microbial flora was studied in 23 patients suffering from culture-positive, symptomatic vaginal candidosis. They were randomly allocated to receive either a 500 mg clotrimazole vaginal pessary or a 150 mg fluconazole capsule. Quantitative microbiological examination was carried out on samples of vaginal secretions obtained prior, and at intervals up to 10 days after, treatment. No significant difference was found in the vaginal flora before or after therapy in individual patients or between the treatment groups. In patients with C glabrata or C krusei, the yeasts persisted longer in the vagina with poorer response to either of the medications.